Sistem Pakar Diagnosa Penyakit Frambusia Menggunakan Metode Fuzzy Tsukamoto - Pasaribu, Rahadian Khairil (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
One of the diseases that is difficult to understand by the general public is Frambusia disease. Frambusia disease is one of the infectious diseases that has not been able to be handled completely Efforts to eradicate Frambusia disease in Indonesia began in 1912 by Kodijat in several districts in Central Java province. therefore an expert system is needed to help handle the dianosis of Frambusia disease to make it faster to find solutions that must be done for the treatment process. In this study, researchers built an expert system for diagnosing Frambusia using Visual Basic Net 2008. The results achieved by the author in this study in applying the Tsukamoto fuzzy method in diagnosing Frambusia disease, and the implementation of the results using the visual basic 2008 application after going through the deffuzyfication stage, the accuracy obtained by the author in this study is 93%.